Ceres Survey Atlas derived from Dawn Framing Camera images. (February 2016) - Roatsch, Th.; Kersten, E.; Matz, K.-D.; Preusker, F.; Scholten, F.; Jaumann, R.; Raymond, C.A.; Russell, C.T.
Abstract: The Dawn Framing Camera (FC) acquired almost 900 clear filter images of Ceres with a resolution of about 400 m/pixels during the seven cycles in the Survey orbit in June 2015. We ortho-rectified 42 images from the third cycle and produced a global, high-resolution, controlled mosaic of Ceres. This global mosaic is the basis for a high-resolution Ceres atlas that consists of 3 tiles mapped at a scale of 1:2, 000, 000. The nomenclature used in this atlas was proposed by the Dawn team and was approved by the International Astronomical Union (IAU). The whole atlas is available to the public through the Dawn GIS web page [http://dawn_gis.dlr.de/atlas ]. Highlights: The mosaic of Ceres was created using camera data from Survey orbit. An atlas of Ceres consisting of three tiles was created. The nomenclature for surface features was approved by the IAU and applied to the atlas.